2012
DOI: 10.1016/j.aap.2010.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for injury accidents among moped and motorcycle riders

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 24 publications
3
53
0
3
Order By: Relevance
“…It has been found that most motorcycle accidents occur while travelling for leisure purposes, but that crash severity is higher for work trips (De Lapparent, 2006;Moskal et al, 2012;Oluwadiya et al, 2009).…”
Section: Motorcyclist Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been found that most motorcycle accidents occur while travelling for leisure purposes, but that crash severity is higher for work trips (De Lapparent, 2006;Moskal et al, 2012;Oluwadiya et al, 2009).…”
Section: Motorcyclist Characteristicsmentioning
confidence: 99%
“…Lin and Kraus, 2009;Moskal et al, 2012;NHTSA, 2007;Savolainen and Mannering, 2007;Shankar, 2003;Shankar and Mannering, 1996), distraction Cheng and Ng, 2010;Elliott et al, 2007;RANDOM, 2005) and fatigue (Peden et al, 2004;Philip et al, 2003;Sanchez, 2001). …”
Section: Motorcyclist Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there have been some studies in other countries correlating environmental and personal variables to accidents the methods used are descriptive in nature. Studies done in Thailand (Stephan et al, 2011), Vietnam (Hsu et al, 2003), Taiwan (Chang and Yeh, 2007), Malaysia (Hsu et al, 2003), Germany (Wick et al, 1998), Denmark (Barsi et al, 2002) and France (Moskal et al, 2012) only showed descriptive statistics of the variables considered and did not seek to determine which of them are significant predictors of accident. Prediction models developed in Indonesia (Indriastuti and Sulistio, 2010), and Iran (Majdzadeh et al, 2008) considered accident prediction but the variables included are very limited.…”
Section: Introductionmentioning
confidence: 99%